1957
DOI: 10.1136/bmj.2.5052.1034
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemia, Amyloidosis, and Renal Vein Thrombosis in Irradiated Ankylosing Spondylitis

Abstract: MEASUREMENT OF GASTRO-INTESTINAL BLEEDING BEMIX At times a lack of correspondence has been observed between the two methods. On the one hand, significant radioactivity has been found with negative benzidine tests (as in days 3 and 4 of Case 2); and on the other, weakly positive benzidine reactions have been observed with no significant radioactivity in the faecal samples. These discrepancies have always been when the amount of blood was small as indicated by one test or the other. Discussion Quantitative chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1960
1960
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Ankylosing spondylitis-though accounting for fewer cases-is also capable of giving rise to it (Enrievaara and Oka, 1963. See also Bayles, 1943 ;Teilum and Lindahl, 1954;Halford and Clark, 1957;Penfold and Rhys-Lewis, 1957;Clinicopathological Conference, 1968). It is of interest that Gillman and Gilbert (1955) encountered generalised amyloidosis in a baboon that suffered from a skeletal disease with some of the features of ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 99%
“…Ankylosing spondylitis-though accounting for fewer cases-is also capable of giving rise to it (Enrievaara and Oka, 1963. See also Bayles, 1943 ;Teilum and Lindahl, 1954;Halford and Clark, 1957;Penfold and Rhys-Lewis, 1957;Clinicopathological Conference, 1968). It is of interest that Gillman and Gilbert (1955) encountered generalised amyloidosis in a baboon that suffered from a skeletal disease with some of the features of ankylosing spondylitis.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of this translocation is unknown, although exposure to ionizing radiation is likely to be a risk factor (7). Previous studies have demonstrated a dose-dependent risk of CML in patients with cancer who undergo radiation therapy (8,9) and experience repeated exposure to diagnostic radiography (7).…”
Section: Introductionmentioning
confidence: 99%